Investigation of a process simulation method for flexible clamping of sheet metal parts - Bauer, Felix; Werber, Alexandra; Merklein, Marion (Procedia Engineering, 2017)
Flexibility in the body-in-white shop can be increased with the use of a running clamping technology, which enables clamping with a welding robot during laser welding. Unlike common clamping fixtures, the running clamping technology is operated force controlled. A closed gap between flanges is necessary to achieve a proper weld seam. The objective of the presented FE-simulation method is to predict required clamping forces to close the gap between sheet metal part flanges with geometrical inaccuracies. For calibration of the simulation model, clamping experiments with simple geometry are used. Steel and aluminum L-specimens are manufactured using air bending and clamped with the running clamping technology. Clamping forces are measured precisely using a load cell, which has been integrated into the running clamping technology. In this contribution a FE-simulation method for process analysis of the flexible clamping process with the running clamping technology is investigated. For clamping simulation, specimens are generated by air bending simulation, as well as by optical measurement of experimentally manufactured specimens. Since specimens are bent during clamping process in the opposite direction of the previous bending process, influences of residual stresses and kinematic hardening on the required clamping forces are expected. Thus, in FE-simulation an elastic-plastic material model with kinematic hardening parameters is used. A mapping method with springback compensation is applied to obtain specimens with optically measured geometry including forming history data of bending simulation. Simulation setups are investigated regarding results of clamping forces. Simulation results are verified using the obtained experimental data.
CRIS-Team Scopus Importer:2023-03-29
Keywords: clamping simulation; finite element method; forming history